Silicon-based negative electrode material and preparation method and application thereof
By reducing the prelithiation temperature of the silicon oxygen negative electrode material and adopting specific treatment methods, SiO/Li2O/TiO2 composite is formed and coated with lithium titanium oxide and carbon layer, the alkaline of the silicon oxygen negative electrode material during the prelithiation process is solved. The problems of enhanced performance, decreased circulation performance and reduced capacity have achieved high capacity, low alkalinity and good circulation performance.
Patent Information
- Application Number
- CN202411667651.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
AI Technical Summary
During the prelithiation process of silicon oxygen negative electrode materials, the problems of alkalinity enhancement, the reduction of cycling performance and the reduction of gram capacity are easily caused by traditional high-temperature prelithiation methods.
By reducing the prelithiation temperature to 450-550°C, the heat absorbing agent system is used to absorb heat to form a SiO/Li2O composite, and spherical titanium dioxide is generated in situ by sol-gel method, and finally a lithium titanium oxide layer is formed during high-temperature calcination. and carbon cladding to ensure that the material does not produce silicate phase and crystalline silicon.
It effectively avoids the increase in alkalinity of the material, reduces capacity loss, improves cycling performance, and improves the first charging and discharging efficiency of lithium-ion batteries.
Smart Images

Figure CN119495729A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of silicon-based negative electrode materials, and in particular relates to a silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] The negative electrode material of lithium battery is an important component of lithium battery. Its performance directly affects the battery capacity. Common negative electrode materials include graphite negative electrode materials, silicon-based negative electrode materials, alloy negative electrode materials, lithium carbonate negative electrode materials, etc. The current market has put forward higher and higher demands on the capacity density of lithium batteries. The theoretical capacity density of graphite negative electrode materials is 372mAh / g, and the theoretical capacity density of silicon-based negative electrode materials is as high as 4199mAh / g. Therefore, it can be expected that with the development of silicon negative electrode materials, the capacity of lithium batteries will usher in a substantial increase.
[0003] Silicon is an active material for the negative electrode. It is easy to expand and shrink during the charge and discharge process, so it is easy to break near the surface. However, the surface rupture of the negative electrode active material will produce a new surface, which will increase the reaction area of the active material. The electrolyte and lithium ions will be further consumed at the new surface to generate a new SEI film, which will lead to reduced cycle performance. Limited by the problem of poor cycle performance due to severe expansion, silicon-oxygen negative electrode materials have become a choice that takes into account both high capacity and low expansion, but silicon-oxygen negative electrode materials have the problem of low first coulomb efficiency performance (first efficiency), which limits their application as negative electrode materials for lithium batteries. In this regard, pre-lithiation and pre-magnesiation are generally used on the market to achieve the purpose of improving the first efficiency of silicon-oxygen negative electrode materials. However, studies have shown that the traditional pre-lithiation method will not only enhance the alkalinity of silicon-oxygen negative electrode materials, but the strong alkalinity will cause the binder to denature during the homogenization process, and will also lead to poor cycle performance and reduced gram capacity. In summary, the key is how to improve the negative effects caused by pre-lithiation silicon oxide negative electrode materials so that they can maintain high charge and discharge capacity performance and first efficiency while having lower alkalinity and better cycle performance. Summary of the invention
[0004] The first object of the present invention is to provide a silicon-based negative electrode material having lower alkalinity, higher charge and discharge capacity performance and first efficiency as well as good cycle performance.
[0005] The second object of the present invention is to provide a method for preparing the above silicon-based negative electrode material.
[0006] The third object of the present invention is to provide a silicon-based negative electrode material prepared by the above method.
[0007] The fourth object of the present invention is to provide application of the above silicon-based negative electrode material in lithium-ion batteries.
[0008] After in-depth and extensive research, the inventors of the present invention found that the main reason why the alkalinity of silicon oxygen negative electrode materials becomes stronger, the charge and discharge capacity decreases, and the cycle performance deteriorates after pre-lithiation using the existing method is that the reaction of pre-lithiation of silicon oxygen negative electrode materials using a lithium source (lithium hydride) is generally carried out at a temperature above 600°C, which not only produces lithium silicate (Li4SiO4), and Li4SiO4 has a strong alkalinity in the water-washed slurry, thereby enhancing the alkalinity of the silicon oxygen negative electrode material, but also causes the silicon oxygen negative electrode material to be converted into crystalline silicon. The growth of crystalline silicon will cause the silicon oxygen negative electrode material to expand and become larger, thereby causing the cycle performance to decrease. At the same time, it will cause the lithium source (lithium hydride) to generate lithium silicate after pre-lithiation. Lithium silicate is a non-electrochemically active phase, and the formation of lithium cobalt oxide will cause the gram capacity to decrease.
[0009] After in-depth research, the inventors of the present invention found that by reducing the pre-lithiation temperature from the existing temperature of more than 600°C to 450-550°C and using an endothermic system to absorb the heat released by the reaction, the reaction of the silicon-oxygen material (silicon oxide) and the lithium source can be stopped at the stage of generating lithium oxide, which can effectively avoid further conversion to generate lithium silicate and form a SiO / Li2O composite. In accordance with this, after pre-lithiation, the titanate compound is diffused into the SiO / Li2O composite by a sol-gel method through a titanate compound and spherical titanium dioxide is generated in situ, and then the obtained SiO / Li2O / TiO2 composite is calcined at a high temperature, and an ion conductor (lithium titanium oxide) can be formed on the surface of the lithium oxide to achieve the encapsulation of the lithium oxide. On this basis, a carbon layer is further coated on the surface of the formed material, and finally a lithium oxide with an ion conductor encapsulated dispersed inside and a silicon oxide composite material with a carbon coating layer on the outer layer is obtained. Thus, on the one hand, the entire preparation process does not generate substances such as Li4SiO4 that may increase the alkalinity of the material, which can keep the material at a relatively low alkalinity; on the other hand, the above preparation process can ensure that no silicate phase is generated and can effectively prevent the growth of silicon crystals, which can reduce capacity loss and improve cycle performance; on the other hand, the negative electrode material formed by the above method has a special structure, which can keep the chemical composition of the generated lithium oxide unchanged during the homogenization process, and release this part of the lithium oxide sealed in the ion conductor through electrochemical reaction during the first cycle of charge and discharge, and at the same time prevent the negative electrode material from reacting with water during the homogenization process, thereby effectively improving the first efficiency of the lithium-ion battery. Based on this, the present invention is completed.
[0010] Specifically, the silicon-based negative electrode material provided by the present invention includes silicon-oxygen material matrix particles, the surface of the silicon-oxygen material matrix particles is coated with a carbon layer and ion conductor-encapsulated lithium oxide particles are dispersed inside, and the ion conductor-encapsulated lithium oxide particles include lithium oxide particles and a lithium titanium oxide layer coated on the surface of the lithium oxide particles.
[0011] The method for preparing the silicon-based negative electrode material provided by the present invention comprises the following steps:
[0012] S1. The silicon oxide material, the lithium source and the endothermic agent are mixed and pre-lithiated at high temperature under the protection of an inert gas, wherein the temperature of the high temperature pre-lithiation is 450°C to 550°C, and after the reaction is completed, the mixture is cooled to room temperature to obtain a SiO / Li2O composite;
[0013] S2. The SiO / Li2O composite and the titanate compound are mixed, and then the titanate compound is diffused into the SiO / Li2O composite by a sol-gel method and spherical titanium dioxide is generated in situ to obtain a SiO / Li2O / TiO2 composite;
[0014] S3. The SiO / Li2O / TiO2 composite is calcined at a high temperature to allow Li2O and TiO2 to react to form a lithium titanium oxide layer on the surface of Li2O, and then a carbon coating layer is formed on the surface of the obtained silicon oxide material matrix particles.
[0015] The present invention reduces the pre-lithiation temperature to 450-550°C, generates spherical titanium dioxide in situ by a sol-gel method, and uses an ion conductor (lithium titanium oxide) to encapsulate lithium oxide, thereby avoiding alkalinity increase while ensuring that no silicate phase is generated in the entire process and preventing silicon crystal growth. This not only reduces capacity loss and improves cycle performance, but also allows the lithium-ion battery to release lithium ions in the first cycle of charge and discharge and prevents lithium ions from reacting with water during the homogenization process, thereby effectively improving the initial efficiency of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the microstructure of the silicon-based negative electrode material obtained in Example 1;
[0017] Figure 2 This is a transmission electron microscope image of the silicon-based negative electrode material obtained in Example 1;
[0018] Figure 3 This is a transmission electron microscope image of the silicon-based negative electrode material obtained in Comparative Example 1;
[0019] Figure 4 This is a transmission electron microscope image of the silicon-based negative electrode material obtained in Comparative Example 2. DETAILED DESCRIPTION
[0020] like Figure 1 As shown, the silicon-based negative electrode material provided by the present invention includes silicon-oxygen material matrix particles, the surface of the silicon-oxygen material matrix particles 101 is coated with a carbon layer 102 and ion conductor-encapsulated lithium oxide particles are dispersed inside, and the ion conductor-encapsulated lithium oxide particles include lithium oxide particles 103 and a lithium titanium oxide layer 104 coated on the surface of the lithium oxide particles 103. Among them, the component of the silicon-oxygen material matrix particles 101 is preferably silicon oxide.
[0021] In the present invention, the particle size of the silicon oxide material matrix particles is preferably 3 to 12 μm, specifically 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 12 μm or any value therebetween. The thickness of the carbon layer is preferably 2 to 5 nm, such as 2 nm, 3 nm, 4 nm, 5 nm or any value therebetween. The particle size of the lithium oxide particles is preferably 10 to 50 nm, such as 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or any value therebetween. The thickness of the lithium titanium oxide layer is preferably 4 to 10 nm, such as 4 nm, 6 nm, 8 nm, 10 nm or any value therebetween.
[0022] In the present invention, the lithium titanium oxide in the lithium titanium oxide layer is preferably D-type lithium titanium oxide.
[0023] In the present invention, amorphous silicon particles are preferably dispersed inside the silicon-oxygen material matrix particles.
[0024] The method for preparing the silicon-based negative electrode material provided by the present invention comprises the following steps:
[0025] S1. The silicon oxide material, the lithium source and the endothermic agent are mixed and pre-lithiated at high temperature under the protection of an inert gas, wherein the temperature of the high temperature pre-lithiation is 450°C to 550°C, and after the reaction is completed, the mixture is cooled to room temperature to obtain a SiO / Li2O composite;
[0026] S2. The SiO / Li2O composite and the titanate compound are mixed, and then the titanate compound is diffused into the SiO / Li2O composite by a sol-gel method and spherical titanium dioxide is generated in situ to obtain a SiO / Li2O / TiO2 composite;
[0027] S3. The SiO / Li2O / TiO2 composite is calcined at a high temperature to allow Li2O and TiO2 to react to form a lithium titanium oxide layer on the surface of Li2O, and then a carbon coating layer is formed on the surface of the obtained silicon oxide material matrix particles.
[0028] In the present invention, in step S1, the silicon-oxygen material can be an unmodified silicon-oxygen material, or a silicon-oxygen material after chemical and / or physical modification. The chemical and physical modification methods can be used as long as they are conducive to the improvement of the charge and discharge capacity performance and / or the first effect and / or the cycle performance of the silicon-oxygen negative electrode material. Particularly preferably, the silicon-oxygen material is a carbon-coated silicon-oxygen material, which can make the lithium oxide formed inside the silicon-based negative electrode material have better stability during the homogenization process, so that the first effect of the obtained lithium-ion battery can be further improved. The carbon content in the carbon-coated silicon-oxygen material is preferably 1.5 to 4.5wt%, such as 1.5wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt% or any value therebetween. The particle size distribution D50 of the carbon-coated silicon oxygen material is preferably 4μm to 8μm, such as 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm or any value therebetween. The carbon-coated silicon oxygen material can be obtained by commercial purchase, or it can be prepared by various existing methods. In a specific embodiment, the carbon-coated silicon oxygen material is prepared according to the following method: under the protection of an inert gas, the silicon oxygen material is put into a rotary kiln and heated to the decomposition temperature of the carbon source, and then the carbon source gas is introduced into the silicon oxygen material so that the carbon source gas decomposes and deposits carbon on the surface of the silicon oxygen material. Among them, the component of the silicon oxygen material is preferably silicon oxide (SiO). The carbon source is preferably acetylene. The heating rate can be, for example, 2 to 8°C / min, such as 2, 4, 6, 8°C / min or any value therebetween. The decomposition temperature of the carbon source is generally 800-900°C, such as 800°C, 820°C, 840°C, 860°C, 880°C, 900°C or any value therebetween.
[0029] In the present invention, in step S1, the type of the lithium source is not particularly limited, as long as it can provide lithium for the negative electrode material, for example, it can be lithium hydride or metallic lithium. However, since the pre-lithiation conditions of metallic lithium are relatively harsh, the pre-lithiation conditions of lithium hydride are relatively low in comparison, therefore, the lithium source is preferably lithium hydride. The amount of the lithium source is preferably 10% to 20% of the mass of the carbon-coated silicon oxide material, such as 10%, 12%, 14%, 16%, 18%, 20% or any value therebetween.
[0030] In the present invention, in step S1, the purpose of adding the endothermic agent is to absorb the heat released by the system to avoid a sharp increase in local temperature and the formation of crystalline silicon, thereby reducing the battery cycle performance. The endothermic agent can undergo an endothermic phase change or an endothermic decomposition reaction at 200 to 800°C. The endothermic phase change or endothermic decomposition reaction temperature of the endothermic agent can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or any value therebetween. Specific examples of the endothermic agent include, but are not limited to, at least one of sodium carbonate, calcium chloride, ferric chloride, zinc chloride, sodium oxalate, magnesium oxalate, calcium lactate and zinc lactate. In addition, the amount of the heat absorber is preferably 30% to 50% of the mass of the carbon-coated silicon oxide material, such as 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50% or any value therebetween.
[0031] In the present invention, in step S1, the temperature of the high-temperature pre-lithiation must be controlled at 450°C to 550°C, and can be specifically 450°C, 470°C, 490°C, 510°C, 530°C, 550°C or any value therebetween. When the temperature of the high-temperature pre-lithiation is lower than 450°C, the pre-lithiation process cannot proceed smoothly; when the temperature of the high-temperature pre-lithiation is higher than 550°C, SiO and Li2O will further react to form lithium silicate, which will affect the electrical properties. When the temperature is higher than 900°C, crystalline silicon will be produced, resulting in a decrease in the cycle performance of the lithium battery. The time of the high-temperature pre-lithiation is preferably 40min to 90min, such as 40min, 50min, 60min, 70min, 80min, 90min or any value therebetween.
[0032] In the present invention, in step S2, the method of using a sol-gel method to diffuse the titanate compound into the interior of the SiO / Li2O complex and generate spherical titanium dioxide in situ can be a conventional choice in the art, and can be an acidic method or an alkaline method, without special limitations. In a specific embodiment, the SiO / Li2O complex and the titanate compound are mixed, and then the sol-gel method is used to diffuse the titanate compound into the interior of the SiO / Li2O complex and generate spherical titanium dioxide in situ. The process includes: dispersing the SiO / Li2O complex and the titanate compound in an organic solvent to obtain slurry A; dispersing glacial acetic acid in a water-organic solvent composite solvent, adjusting the pH value of the obtained dispersion to 2 to 4, and obtaining solution B; slowly introducing slurry A into solution B for sol-gel in-situ reaction, and drying after the reaction is completed. The solid content of the slurry A is preferably 20% to 50%, such as 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50% or any value therebetween. Specific examples of the titanate compound include, but are not limited to, at least one of tetrabutyl titanate, tetra-tert-butyl titanate, tetraethyl titanate and tetraisopropyl titanate. The dosage of the titanate compound is preferably 15 to 40 wt% of the mass of the SiO / Li2O composite, such as 15 wt%, 18 wt%, 20 wt%, 22 wt%, 25 wt%, 28 wt%, 30 wt%, 32 wt%, 35 wt%, 38 wt%, 40 wt% or any value therebetween. The volume ratio of glacial acetic acid, water and organic solvent in the solution B is preferably (1-3): (5-15): 100, such as 1:5: 100, 1:8: 100, 1:10: 100, 1:12: 100, 1:15: 100, 2:5: 100, 2:8: 100, 2:10: 100, 2:12: 100, 2:15: 100, 3:5: 100, 3:8: 100, 3:10: 100, 3:12: 100, 3:15: 100, etc. The volume ratio of the slurry A and the solution B is preferably (0.9-1.1): 1, such as 0.9: 1, 1: 1, 1.1: 1 or any value therebetween. The organic solvent in the slurry A and the slurry B can be various existing inert liquid media, for example, can be selected from at least one of an alcohol solvent, an ester solvent and an ether solvent. The method of adjusting the pH value of the dispersion to 2-4 may include, for example, adding an acid solution dropwise to the dispersion, wherein the acid solution may be, for example, at least one of hydrochloric acid, dilute sulfuric acid, nitric acid and phosphoric acid.In addition, the conditions for the sol-gel in-situ reaction preferably include a temperature of 40 to 60°C, such as 40°C, 42°C, 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C or any value therebetween; a time of 30min to 60min, such as 30min, 35min, 40min, 45min, 50min, 55min, 60min or any value therebetween. The conditions for the drying preferably include a temperature of 50°C to 70°C, such as 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C or any value therebetween; a time of 12h to 16h, such as 12h, 13h, 14h, 15h, 16h or any value therebetween.
[0033] In the present invention, in step S3, the conditions of the high temperature calcination preferably include a temperature of 540 to 680°C and a time of 50 to 180 min. The high temperature calcination temperature may specifically be 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C or any value therebetween. When the temperature of the high temperature calcination is higher than 680°C, crystalline silicon will be produced, which will affect the cycle performance of the lithium battery; when the temperature of the high temperature calcination is lower than 540°C, the reaction will remain at the stage of producing lithium oxide and will not continue to react to generate lithium silicate. In addition, controlling the temperature of the high temperature calcination at 540 to 680°C can effectively decompose the carbon source gas into carbon to achieve coating of the surface of the silicon-oxygen material matrix particles. The time of the high temperature calcination may specifically be 50 min, 60 min, 80 min, 100 min, 120 min, 140 min, 160 min, 180 min or any value therebetween.
[0034] In the present invention, in step S3, the process of forming a carbon coating layer on the surface of the silicon-oxygen material matrix particles includes: under the protection of an inert gas, heating the silicon-oxygen material matrix particles to the decomposition temperature of the carbon source gas, and then introducing the carbon source gas into the silicon-oxygen material matrix particles so that the carbon source gas decomposes and deposits carbon on the surface of the silicon-oxygen material matrix particles, and naturally cools to room temperature and then screens. The heating rate is preferably 2°C / min to 5°C / min, such as 2, 3, 4, 5°C / min or any value therebetween. The temperature at which the carbon source gas decomposes is preferably 580°C to 640°C, such as 580°C, 600°C, 620°C, 640°C or any value therebetween. The carbon source gas can be, for example, acetylene. The gas flow rate of the carbon source gas is preferably 150mL / min to 300mL / min, such as 150, 180, 200, 220, 240, 260, 280, 300mL / min or any value therebetween; the ventilation time of the carbon source gas is preferably 60min to 120min, such as 60min, 70min, 80min, 90min, 100min or any value therebetween. The sieve particle size of the sieving is preferably 200 to 500 mesh, such as 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 420 mesh, 440 mesh, 460 mesh, 480 mesh, 500 mesh or any value therebetween.
[0035] In the present invention, the inert gas may be argon and / or a group 0 gas, wherein the group 0 gas includes at least one of helium, neon and argon.
[0036] The preparation method of the silicon-based negative electrode material provided by the present invention preferably also includes, after stopping the introduction of the carbon source gas, continuing to keep warm at the decomposition temperature of the carbon source gas for a period of time, at this time, not only can the carbon source gas adsorbed on the surface of the negative electrode material continue to decompose, but also can make the dimers, trimers and other impurities produced by the decomposition of the carbon source gas that affect the activity of the lithium ion battery at least partially volatilize, so as not to affect the battery performance, thereby giving the lithium ion battery better charge and discharge capacity performance, first effect and cycle performance. Wherein, the insulation time is preferably 30min to 60min, such as 30min, 35min, 40min, 45min, 50min, 55min, 60min or any value therebetween.
[0037] The present invention also provides a silicon-based negative electrode material prepared by the above method.
[0038] The present invention also provides application of the silicon-based negative electrode material in lithium-ion batteries.
[0039] The present invention will be described in detail below through examples.
[0040] Preparation Example 1 Preparation of Carbon-coated Silicon Oxygen Material
[0041] 3 kg of silicon oxide material (component: SiO, purchased from Hengshui Chaofan New Energy Technology Co., Ltd., brand: MSP-5) was put into a rotary kiln, nitrogen was introduced to drive out oxygen for 1 hour, and then the temperature was raised to 850°C at a rate of 5°C / min. After reaching 850°C, acetylene gas was introduced and kept warm for 1 hour. After the insulation was completed, the acetylene gas was stopped and the mixture was naturally cooled to room temperature to obtain amorphous carbon-coated silicon oxide material particles with a particle size distribution D50 of 6 μm and a carbon content of 1.7 wt%.
[0042] Preparation Example 2 Preparation of Carbon-coated Silicon Oxygen Material
[0043] Carbon-coated silicon-oxygen material was prepared according to the method of Preparation Example 1, except that the acetylene gas was introduced for 2.5 h to obtain amorphous carbon-coated silicon-oxygen material particles with a particle size distribution D50 of 6.2 μm and a carbon content of 4.5 wt%.
[0044] Preparation Example 3 Preparation of Carbon-coated Silicon Oxygen Material
[0045] Carbon-coated silicon-oxygen material was prepared according to the method of Preparation Example 1, except that the acetylene gas was introduced for 2 h to obtain amorphous carbon-coated silicon-oxygen material particles with a particle size distribution D50 of 6.1 μm and a carbon content of 3 wt%.
[0046] Example 1 Silicon-based negative electrode material
[0047] S1. 100 g of carbon-coated silicon oxide material particles (prepared in Preparation Example 1, with a carbon content of 1.7 wt%), 20 g of lithium hydride (LiH), 20 g of calcium chloride and 20 g of zinc lactate were mixed evenly, sintered at 480° C. for 60 min in an argon atmosphere, and naturally cooled to room temperature to obtain a SiO / Li2O composite.
[0048] S2. Disperse 80g of SiO / Li2O complex into 200mL of ethanol solution, slowly add 20g of tetrabutyl titanate under ultrasonic dispersion conditions, continue ultrasonication and stirring to mix evenly, and obtain slurry A. Add 4mL of glacial acetic acid and 20mL of deionized water to another 200mL of anhydrous ethanol and stir vigorously, add 4-8 drops of 3M hydrochloric acid to adjust the pH to 3, and obtain solution B. Slurry A is slowly introduced into solution B under ultrasonication at 40℃ water bath, and the water bath reaction is continued for 60min after the introduction. After the reaction is completed, vacuum dry at 60℃ for 12h to obtain SiO / Li2O / TiO2 complex.
[0049] S3. The SiO / Li2O / TiO2 composite was transferred to a rotary kiln, and the temperature was raised to 600°C at a rate of 3°C / min under nitrogen protection and kept warm for 180 min. Then, acetylene gas was introduced (gas flow rate was 200 mL / min). After 90 min, the acetylene gas was turned off, and the mixture was kept warm for 50 min. Then, the mixture was naturally cooled to room temperature. After discharging, the mixture was sieved with a 325-mesh sieve to obtain a silicon-based negative electrode material.
[0050] The silicon-based negative electrode material is prepared by low-temperature pre-lithiation, and its transmission electron microscope (TEM) is as follows Figure 2 As shown, from Figure 2 It can be seen that the silicon-based negative electrode material does not contain crystalline silicon.
[0051] The results of focused ion beam scanning electron microscopy (SEM-FIB) and X-ray powder diffraction (XRD) of the silicon-based negative electrode material show that it includes a silicon oxide material matrix (silicon oxide), the surface of the silicon oxide material matrix particles is coated with a carbon layer and ion conductor encapsulated lithium oxide particles are dispersed inside, and the ion conductor encapsulated lithium oxide particles include lithium oxide particles and a lithium titanium oxide layer coated on the surface of the lithium oxide particles. Among them, the particle size of the silicon oxide material matrix particles is 4 to 8 μm. The thickness of the carbon layer is 2 to 5 nm. The particle size of the lithium oxide particles is 30 to 50 nm. The thickness of the lithium titanium oxide layer is 4 to 8 nm. Characterized by an X-ray diffractometer (XRD), the lithium titanium oxide in the lithium titanium oxide layer is D-type lithium titanium oxide.
[0052] Example 2 Silicon-based negative electrode material
[0053] S1. 100 g of carbon-coated silicon oxide material particles (prepared in Preparation Example 2, with a carbon content of 4.5 wt%), 15 g of lithium hydride (LiH), 15 g of zinc chloride and 15 g of sodium oxalate were mixed evenly, sintered at 450° C. for 90 min in an argon atmosphere, and naturally cooled to room temperature to obtain a SiO / Li2O composite.
[0054] S2. Disperse 80g of SiO / Li2O complex into 200mL of ethanol solution, slowly add 15g of tetraisopropyl titanate under ultrasonic dispersion conditions, continue ultrasonication and stirring to mix evenly, and obtain slurry A. Add 4mL of glacial acetic acid and 20mL of deionized water to another 200mL of anhydrous ethanol and stir vigorously, add 4-8 drops of 3M hydrochloric acid to adjust the pH to 4, and obtain solution B. Slurry A is slowly introduced into solution B under ultrasonication at 60℃ water bath, and the water bath reaction is continued for 30min after the introduction. After the reaction is completed, vacuum dry at 60℃ for 12h to obtain SiO / Li2O / TiO2 complex.
[0055] S3. The SiO / Li2O / TiO2 composite was transferred to a rotary kiln, and the temperature was raised to 640°C at a rate of 3°C / min under nitrogen protection and kept warm for 50 minutes. Then, acetylene gas was introduced (gas flow rate was 200 mL / min). After 90 minutes, the acetylene gas was turned off, and the mixture was kept warm for 50 minutes. Then, the mixture was naturally cooled to room temperature. After discharging, the mixture was sieved with a 325-mesh sieve to obtain a silicon-based negative electrode material.
[0056] The silicon-based negative electrode material is prepared by low-temperature pre-lithiation, and its transmission electron microscope image shows that the silicon-based negative electrode material does not contain crystalline silicon.
[0057] The SEM-FIB and XRD results of the silicon-based negative electrode material show that it includes a silicon-oxygen material matrix (silicon oxide), the surface of the silicon-oxygen material matrix particles is coated with a carbon layer and ion conductor-encapsulated lithium oxide particles are dispersed inside, and the ion conductor-encapsulated lithium oxide particles include lithium oxide particles and a lithium titanium oxide layer coated on the surface of the lithium oxide particles. Among them, the particle size of the silicon-oxygen material matrix particles is 4 to 8 μm. The thickness of the carbon layer is 2 to 5 nm. The particle size of the lithium oxide particles is 30 to 50 nm. The thickness of the lithium titanium oxide layer is 4 to 8 nm. According to XRD characterization, the lithium titanium oxide in the lithium titanium oxide layer is D-type lithium titanium oxide.
[0058] Example 3 Silicon-based negative electrode material
[0059] S1. 100 g of carbon-coated silicon oxide material particles (prepared in Preparation Example 3, with a carbon content of 3 wt%), 20 g of lithium hydride (LiH) and 50 g of calcium lactate were mixed evenly, sintered at 550° C. for 40 min in an argon atmosphere, and naturally cooled to room temperature to obtain a SiO / Li2O composite.
[0060] S2. Disperse 80g of SiO / Li2O complex into 200mL of ethanol solution, slowly add 15g of tetraethyl titanate under ultrasonic dispersion conditions, continue ultrasonication and stirring to mix evenly, and obtain slurry A. Add 4mL of glacial acetic acid and 20mL of deionized water to another 200mL of anhydrous ethanol and stir vigorously, add 4-8 drops of 3M hydrochloric acid to adjust the pH to 2, and obtain solution B. Slurry A is slowly introduced into solution B under 50℃ water bath while ultrasonication, and the water bath reaction is continued for 40min after the introduction. After the reaction is completed, vacuum dry at 70℃ for 14h to obtain SiO / Li2O / TiO2 complex.
[0061] S3. The SiO / Li2O / TiO2 composite was transferred to a rotary kiln, and the temperature was raised to 680°C at a rate of 3°C / min under nitrogen protection and kept warm for 50 minutes. Then, acetylene gas was introduced (gas flow rate was 200 mL / min). After 90 minutes, the acetylene gas was turned off, and the mixture was kept warm for 50 minutes. Then, the mixture was naturally cooled to room temperature. After discharging, the mixture was sieved with a 325-mesh sieve to obtain a silicon-based negative electrode material.
[0062] The silicon-based negative electrode material is prepared by low-temperature pre-lithiation, and its transmission electron microscope image shows that the silicon-based negative electrode material does not contain crystalline silicon.
[0063] The SEM-FIB and XPS results of the silicon-based negative electrode material show that it includes a silicon oxide material matrix (silicon oxide), the surface of the silicon oxide material matrix particles is coated with a carbon layer and ion conductor encapsulated lithium oxide particles are dispersed inside, and the ion conductor encapsulated lithium oxide particles include lithium oxide particles and a lithium titanium oxide layer coated on the surface of the lithium oxide particles. Among them, the particle size of the silicon oxide material matrix particles is 4 to 8 μm. The thickness of the carbon layer is 2 to 5 nm. The particle size of the lithium oxide particles is 30 to 50 nm. The thickness of the lithium titanium oxide layer is 4 to 8 nm. According to XRD characterization, the lithium titanium oxide in the lithium titanium oxide layer is D-type lithium titanium oxide.
[0064] Example 4 Silicon-based negative electrode material
[0065] A silicon-based negative electrode material was prepared according to the method of Example 1, except that the carbon-coated silicon oxide material particles were replaced by the same weight portion of silicon oxide material (component: SiO, purchased from Hengshui Chaofan New Energy Technology Co., Ltd., brand: MSP-5), and the other conditions were the same as in Example 1 to obtain a silicon-based negative electrode material.
[0066] The silicon-based negative electrode material is prepared by low-temperature pre-lithiation, and its transmission electron microscope image shows that the silicon-based negative electrode material does not contain crystalline silicon.
[0067] The SEM-FIB and XPS results of the silicon-based negative electrode material show that it includes a silicon oxide material matrix (silicon oxide), the surface of the silicon oxide material matrix particles is coated with a carbon layer and ion conductor encapsulated lithium oxide particles are dispersed inside, and the ion conductor encapsulated lithium oxide particles include lithium oxide particles and a lithium titanium oxide layer coated on the surface of the lithium oxide particles. Among them, the particle size of the silicon oxide material matrix particles is 4 to 8 μm. The thickness of the carbon layer is 2 to 5 nm. The particle size of the lithium oxide particles is 30 to 50 nm. The thickness of the lithium titanium oxide layer is 4 to 8 nm. According to XRD characterization, the lithium titanium oxide in the lithium titanium oxide layer is D-type lithium titanium oxide.
[0068] Example 5 Silicon-based negative electrode material
[0069] The silicon-based negative electrode material was prepared according to the method of Example 1, except that in step S2, after the acetylene gas was turned off, the reaction was not kept warm, but directly cooled naturally to room temperature. After the material was discharged, it was sieved with a 325-mesh sieve to obtain the silicon-based negative electrode material.
[0070] The silicon-based negative electrode material is prepared by low-temperature pre-lithiation, and its transmission electron microscope image shows that the silicon-based negative electrode material does not contain crystalline silicon.
[0071] The SEM-FIB and XPS results of the silicon-based negative electrode material show that it includes a silicon oxide material matrix (silicon oxide), the surface of the silicon oxide material matrix particles is coated with a carbon layer and ion conductor encapsulated lithium oxide particles are dispersed inside, and the ion conductor encapsulated lithium oxide particles include lithium oxide particles and a lithium titanium oxide layer coated on the surface of the lithium oxide particles. Among them, the particle size of the silicon oxide material matrix particles is 4 to 8 μm. The thickness of the carbon layer is 2 to 5 nm. The particle size of the lithium oxide particles is 30 to 50 nm. The thickness of the lithium titanium oxide layer is 4 to 8 nm. According to XRD characterization, the lithium titanium oxide in the lithium titanium oxide layer is D-type lithium titanium oxide.
[0072] Comparative Example 1
[0073] 100 g of carbon-coated silicon oxide material (prepared in Preparation Example 1, with a carbon content of 1.7 wt%) was mixed evenly with 20 g of LiH, sintered at 680° C. for 60 min in an argon atmosphere, naturally cooled to room temperature, and sieved with a 325-mesh sieve to obtain a silicon-based negative electrode material.
[0074] The silicon-based negative electrode material is prepared by traditional high-temperature pre-lithiation. Figure 3 As shown, from Figure 3 It can be seen that there are a large number of large-sized silicon crystals inside the silicon-based negative electrode material.
[0075] Comparative Example 2
[0076] The silicon-based negative electrode material is prepared according to the method of Example 1, except that in step S1, no heat absorbent is added to absorb heat. The specific steps are as follows:
[0077] S1. 100 g of carbon-coated silicon oxide material particles (prepared in Preparation Example 1, with a carbon content of 1.7 wt%) and 20 g of lithium hydride (LiH) were mixed uniformly, sintered at 480 ° C for 60 min in an argon atmosphere, and naturally cooled to room temperature to obtain a SiO / Li2O composite;
[0078] S2. Disperse 80g of SiO / Li2O complex into 200mL of ethanol solution, slowly add 20g of tetrabutyl titanate under ultrasonic dispersion conditions, continue ultrasonication and stirring to mix evenly, and obtain slurry A. Add 4mL of glacial acetic acid and 20mL of deionized water to another 200mL of anhydrous ethanol and stir vigorously, add 4-8 drops of 3M hydrochloric acid to adjust the pH to 3, and obtain solution B. Slurry A is slowly introduced into solution B under ultrasonication at 40℃ water bath, and the water bath reaction is continued for 60min after the introduction. After the reaction is completed, vacuum dry at 60℃ for 12h to obtain SiO / Li2O / TiO2 complex.
[0079] S3. The SiO / Li2O / TiO2 composite was transferred to a rotary kiln, and the temperature was raised to 600°C at a rate of 3°C / min under nitrogen protection and kept warm for 50 minutes. Then, acetylene gas was introduced (gas flow rate was 200 mL / min). After 90 minutes, the acetylene gas was turned off, and the mixture was kept warm for 50 minutes. Then, the mixture was naturally cooled to room temperature. After discharging, the mixture was sieved with a 325-mesh sieve to obtain a silicon-based negative electrode material.
[0080] The silicon-based negative electrode material is pre-lithiated without adding a heat absorber, and its transmission electron microscope image is as follows Figure 4 As shown, from Figure 4 It can be seen that there are a large number of small-sized silicon crystals inside the silicon-based negative electrode material.
[0081] Comparative Example 3
[0082] The silicon-based negative electrode material was prepared according to the method of Example 1, except that the lithium oxide was not encapsulated with lithium titanium oxide. The specific steps were as follows:
[0083] 100 g of carbon-coated silicon oxide material particles (prepared in Preparation Example 1, with a carbon content of 1.7 wt%), 20 g of lithium hydride (LiH), 20 g of calcium chloride and 20 g of zinc lactate were mixed evenly, sintered at 480 ° C for 60 min in an argon atmosphere, cooled naturally to room temperature, and sieved with a 325 mesh sieve to obtain a SiO / Li2O composite.
[0084] Comparative Example 4
[0085] The silicon-based negative electrode material is prepared according to the method of Example 1, except that in step S2, high-temperature calcination and formation of a carbon coating layer on the surface are not performed. The specific steps are as follows:
[0086] S1. 100 g of carbon-coated silicon oxide material particles (prepared in Preparation Example 1, with a carbon content of 1.7 wt%), 20 g of lithium hydride (LiH), 20 g of calcium chloride and 20 g of zinc lactate were mixed uniformly, sintered at 480 ° C for 60 min in an argon atmosphere, and naturally cooled to room temperature to obtain a SiO / Li2O composite;
[0087] S2. Disperse 80g of SiO / Li2O complex into 200mL of ethanol solution, slowly add 20g of tetrabutyl titanate under ultrasonic dispersion conditions, continue ultrasonication and stirring to mix evenly, and obtain slurry A. Add 4mL of glacial acetic acid and 20mL of deionized water to another 200mL of anhydrous ethanol and stir vigorously, add 4-8 drops of 3M hydrochloric acid to adjust the pH to 3, and obtain solution B. Slurry A is slowly introduced into solution B under ultrasonication at 40℃ water bath, and the water bath reaction is continued for 60min after the introduction. After the reaction is completed, vacuum dry at 60℃ for 12h to obtain silicon-based negative electrode material.
[0088] Test Case
[0089] The silicon-oxygen negative electrode materials obtained in the above examples and comparative examples were subjected to alkalinity test, charge-discharge capacity performance, first efficiency and cycle performance tests according to the following methods. The results are shown in Table 1.
[0090] (1) Alkaline test:
[0091] 10 g of the silicon-oxygen negative electrode material obtained in the above examples and comparative examples were dispersed in 100 mL of pure water, respectively, and filtered after ultrasonic stirring for 30 min. The filtrate was taken to test the pH value with a pH meter.
[0092] (2) Charge and discharge capacity performance and initial efficiency and cycle performance test:
[0093] The double-electrode button cell was assembled according to the following method: acetylene black (AB) was used as a conductive agent and carboxymethyl cellulose (CMC) was used as a binder. The conductive agent, binder and active material (silicon oxide negative electrode material) were dissolved in deionized water at a mass ratio of 15:15:70 and dispersed evenly. The obtained battery slurry was then coated on the surface of the copper foil, dried at 120°C in a vacuum environment for 12 hours, and then rolled to obtain the pole piece. The thickness of the pole piece after drying was about 60μm, and the actual mass load of the active material in each 10 pole pieces was about 1.2mg / cm 2 The test cell was assembled in an argon-filled glove box, with metal lithium foil as the counter electrode, porous polypropylene (Celgard2400) film as the separator, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, where EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 1:1) as the electrolyte to obtain a double-electrode button cell.
[0094] The double-electrode button cell was placed at 25°C for 6 hours, then charged at 0.1C constant current to a cut-off voltage of 1.5V, and the charging capacity was recorded; it was discharged at 0.1C constant current to 0.01V, and then deeply discharged at 0.01C to 0.005V, and the discharge capacity was recorded, from which the charging capacity, discharge capacity and first coulomb efficiency can be calculated. Among them, first coulomb efficiency = charging gram capacity / discharging gram capacity × 100%.
[0095] At room temperature, charge and discharge cycles were performed 50 times at a current density of 0.5C in the voltage range of 3.0 to 4.6V to examine the capacity retention rate of the positive electrode material.
[0096] Table 1
[0097]
[0098] It can be seen from the data in Table 1 that the lithium-ion battery corresponding to the silicon-oxygen negative electrode material obtained by the method provided by the present invention has higher charge and discharge gram capacity and first efficiency and better cycle performance. In addition, compared with the traditional high-temperature pre-lithiation to form a silicate phase, the silicon-oxygen negative electrode material obtained by the method provided by the present invention has lower alkalinity.
[0099] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material includes silicon-oxygen material matrix particles, the surface of the silicon-oxygen material matrix particles is coated with a carbon layer and ion conductor-encapsulated lithium oxide particles are dispersed inside, and the ion conductor-encapsulated lithium oxide particles include lithium oxide particles and a lithium titanium oxide layer coated on the surface of the lithium oxide particles.
2. The silicon-based negative electrode material according to claim 1, characterized in that: The particle size of the silicon-oxygen material matrix particles is 3 to 12 μm; the thickness of the carbon layer is 2 to 5 nm.
3. The silicon-based negative electrode material according to claim 1 or 2, characterized in that: The particle size of the lithium oxide particles is 10 to 50 nm; the thickness of the lithium titanium oxide layer is 4 to 10 nm.
4. The silicon-based negative electrode material according to claim 1 or 2, characterized in that: The silicon-oxygen material matrix particles are composed of silicon oxide.
5. The silicon-based negative electrode material according to claim 1 or 2, characterized in that: Amorphous silicon particles are also dispersed inside the silicon-oxygen material matrix particles.
6. A method for preparing a silicon-based negative electrode material, characterized in that: The method comprises the following steps: S1. The silicon oxide material, the lithium source and the endothermic agent are mixed and pre-lithiated at high temperature under the protection of an inert gas, wherein the temperature of the high temperature pre-lithiation is 450°C to 550°C, and after the reaction is completed, the mixture is cooled to room temperature to obtain a SiO / Li2O composite; S2. The SiO / Li2O composite and the titanate compound are mixed, and then the titanate compound is diffused into the SiO / Li2O composite by a sol-gel method and spherical titanium dioxide is generated in situ to obtain a SiO / Li2O / TiO2 composite; S3. The SiO / Li2O / TiO2 composite is calcined at a high temperature to allow Li2O and TiO2 to react to form a lithium titanium oxide layer on the surface of Li2O, and then a carbon coating layer is formed on the surface of the obtained silicon oxide material matrix particles.
7. The method for preparing a silicon-based negative electrode material according to claim 6, characterized in that: In step S1, the silicon-oxygen material is a carbon-coated silicon-oxygen material; Preferably, the carbon content in the carbon-coated silicon-oxygen material is 1.5 to 4.5 wt %; Preferably, the particle size distribution D50 of the carbon-coated silicon oxide material is 4 μm to 8 μm; Preferably, the lithium source is lithium hydride; Preferably, the amount of the lithium source is 10% to 20% of the mass of the carbon-coated silicon-oxygen material; Preferably, the endothermic agent can undergo an endothermic phase change or endothermic decomposition reaction at 200 to 800°C; Preferably, the heat absorbent is selected from at least one of sodium carbonate, calcium chloride, ferric chloride, zinc chloride, sodium oxalate, magnesium oxalate, calcium lactate and zinc lactate; Preferably, the amount of the heat absorbent is 30% to 50% of the mass of the carbon-coated silicon-oxygen material; Preferably, the high-temperature pre-lithiation time is 40 min to 90 min.
8. The method for preparing a silicon-based negative electrode material according to claim 6, characterized in that: In step S2, the SiO / Li2O complex and the titanate compound are mixed, and then the titanate compound is diffused into the SiO / Li2O complex by a sol-gel method to generate spherical titanium dioxide in situ, which includes: dispersing the SiO / Li2O complex and the titanate compound in an organic solvent to obtain slurry A; dispersing glacial acetic acid in a water-organic solvent composite solvent, adjusting the pH value of the obtained dispersion to 2-4, and obtaining solution B; slowly introducing slurry A into solution B for sol-gel in-situ reaction, and drying after the reaction is completed; Preferably, the solid content of the slurry A is 20% to 50%; Preferably, the titanate compound is selected from at least one of tetrabutyl titanate, tetra-tert-butyl titanate, tetraethyl titanate and tetraisopropyl titanate; Preferably, the titanate compound is added in an amount of 15 to 40 wt% of the mass of the SiO / Li2O composite; Preferably, the volume ratio of glacial acetic acid, water and organic solvent in the solution B is (1-3):(5-15):100; Preferably, the volume ratio of the slurry A to the solution B is (0.9-1.1):1; Preferably, the conditions of the sol-gel in-situ reaction include a temperature of 40 to 60° C. and a time of 30 to 60 min; Preferably, the drying conditions include a temperature of 50° C. to 70° C. and a drying time of 12 h to 16 h.
9. The method for preparing a silicon-based negative electrode material according to claim 6, characterized in that: In step S3, the high temperature calcination is carried out at a temperature of 540 to 680° C. and a time of 50 to 180 min.
10. The method for preparing a silicon-based negative electrode material according to claim 7, characterized in that: In step S3, the process of forming a carbon coating layer on the surface of the silicon-oxygen material matrix particles includes: under the protection of an inert gas, heating the silicon-oxygen material matrix particles to a decomposition temperature of a carbon source gas, introducing a carbon source gas into the silicon-oxygen material matrix particles so that the carbon source gas decomposes and deposits carbon on the surface of the silicon-oxygen material matrix particles, and naturally cooling to room temperature before screening; Preferably, the heating rate is 2°C / min to 5°C / min; Preferably, the temperature of decomposition of the carbon source gas is 580°C to 640°C; Preferably, the carbon source gas is acetylene; Preferably, the gas flow rate of the carbon source gas is 150 mL / min to 300 mL / min, and the ventilation time of the carbon source gas is 60 min to 120 min; Preferably, the sieve particle size of the sieving is 200-500 mesh; Preferably, the method for preparing the silicon-based negative electrode material further comprises, after stopping the introduction of the carbon source gas, continuing to keep the temperature at the decomposition temperature of the carbon source gas for a period of time; Preferably, the insulation time is 30 min to 60 min.
11. A silicon-based negative electrode material prepared by the method according to any one of claims 6 to 10.
12. Use of the silicon-based negative electrode material according to any one of claims 1 to 5 and 11 in a lithium battery.